An annotated checklist of anomuran species (Crustacea: Decapoda) of India - Patel, Krupal; Padate, Vinay; Osawa, Masayuki; Tiwari, Shivam; Vachhrajani, Kauresh; Trivedi, Jigneshkumar (Zootaxa, 2022)
An annotated checklist of the anomuran crustaceans recorded from Indian waters is compiled from available published literature. A total of 231 species belonging to 58 genera, 15 families and five superfamilies are listed. The highest number of species was seen in the Andaman and Nicobar Islands Ecoregion (114 species, 37 genera, 14 families), followed by the South India Ecoregion (111 species, 41 genera, 14 families), West India Ecoregion (93 species, 36 genera, 14 families), Eastern India Ecoregion (76 species, 29 genera, 12 families), Maldives Ecoregion (34 species, 15 genera, 10 families) and Northern Bay of Bengal Ecoregion (22 species, nine genera, five families). Notes on the questionable identifications and records of some anomuran crabs are also provided.